2013
DOI: 10.1016/j.epsl.2013.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and isotope ratios of helium and other noble gases in the Earth's atmosphere during 1978–2011

Abstract: The evolution of the atmospheric noble gas composition during the past few decades has hardly been studied because, in contrast to many other atmospheric gases, systematic time-series measurements have not been available. Based on theoretical considerations, the atmospheric noble gas isotope composition is assumed to be stable on time scales of up to about 10 6 years, with the potential exception of anthropogenic changes predicted for the He concentration and the 3 He/ 4 He ratio.However, experimental assessme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 27 publications
0
45
4
Order By: Relevance
“…The He isotope residence time in the atmosphere is of the order of 10 4 -10 6 yr (Torgersen, 1989;Kockarts, 1973), much longer than the atmospheric mixing time of 10 yr. Thus, the 3 He/ 4 He ratio of modern air (1.34-1.40 × 10 −6 , Mamyrin et al, 1970;Clarke et al, 1976;Davidson and Emerson, 1990;Hoffman and Nier, 1993;Sano and Wakita, 1988) should be constant on a decadal timescale. However, it has been suggested that this may no longer be the case (Sano et al, 1989;Pierson-Wickmann et al, 2001;Brennwald et al, 2013;Lupton and Evans, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The He isotope residence time in the atmosphere is of the order of 10 4 -10 6 yr (Torgersen, 1989;Kockarts, 1973), much longer than the atmospheric mixing time of 10 yr. Thus, the 3 He/ 4 He ratio of modern air (1.34-1.40 × 10 −6 , Mamyrin et al, 1970;Clarke et al, 1976;Davidson and Emerson, 1990;Hoffman and Nier, 1993;Sano and Wakita, 1988) should be constant on a decadal timescale. However, it has been suggested that this may no longer be the case (Sano et al, 1989;Pierson-Wickmann et al, 2001;Brennwald et al, 2013;Lupton and Evans, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Thereby, variation of the atmospheric helium isotope ratio ( 3 He/ 4 He) has been proposed as a possible new atmospheric tracer of industrial activity. However, the magnitude of such change is debated, with possible values ranging from 0 to about 2h/yr (Sano et al, 1989;Hoffman and Nier, 1993;Pierson-Wickmann et al, 2001;Brennwald et al, 2013;Lupton and Evans, 2013). A new analytical facility for high precision (2h, 2σ ) analysis of the 3 He/ 4 He ratio of air has been developed at CRPG Nancy (France) capable of investigating permil level…”
mentioning
confidence: 99%
“…The Lott and Jenkins is solubility ∼2 % higher than published data from Weiss (1971). The He solubility is for bulk He and we calculate the 3 He solubility using an atmosperic mole ratio ( ( Mamyrin et al, 1970;Porcelli et al, 2002), although some more recent results indicate the current ratio may be slightly lower, ≃1.390 x 10 −6 (Brennwald et al, 2013b). We use the He equilibrium isotopic fractionation as described in Benson and Krause (1980b).…”
Section: Measurement Of 3 Hementioning
confidence: 99%
“…According to Oliver et al (1984), the exploitation of natural gases (NG) could have increased the global atmospheric helium content by 1 to 6 ‰ between 1939 and 1981. Because NG are rich in radiogenic 4 He generated in the continental crust, the R AIR could have decreased by ≤3 ‰/yr (Brennwald et al, 2013 and references therein; see also Fig. S-1).…”
Section: Introductionmentioning
confidence: 99%